Effects of Perceived Parent–Child Relationships and Self-Concept on Creative Personality among Middle School Students - Hyesung Park; Sungyeun Kim (Behavioral Sciences, 2024)
This study investigated the impact of perceived parent–child relationships on creative personality in middle school students according to self-concept, focusing on environmental (parent–child relationships) and individual (self-concept) factors that can influence these students’ creative personalities. To this end, this study verified the moderation effect using sixth-year data (third year of middle school students) from the Seoul Longitudinal Educational Study 2010 Panel, utilizing SPSS 26.0 and the PROCESS macro. The results revealed that the self-concept of middle school students moderated the influence of parent–child relationships on creative personality. Specifically, it was found that as the level of self-concept increased above the average the positive relationship between parent–child relationships and creative personality strengthened. Based on the study’s findings, theoretical and practical suggestions for creating a home and educational environment to promote creativity during adolescence were discussed.